Proceedings from the 2nd Next Gen Therapies for Systemic Juvenile Idiopathic Arthritis and Macrophage Activation Syndrome symposium held on October 3-4, 2019 - Scott W. Canna; Grant S. Schulert; Adriana de Jesus; Alex Pickering; Hermine Brunner; Massimo Gadina; Stewart Levine; Raphaela Goldbach-Mansky; Jonathan Boutelle; Rashmi Sinha; Fabrizio DeBenedetti; Alexei Grom; et al. (BMC, 2020)
Abstract For reasons poorly understood, and despite the availability of biological medications blocking IL-1 and IL-6 that have markedly improved overall disease control, children with Systemic Juvenile Idiopathic Arthritis (SJIA) are now increasingly diagnosed with life-threatening chronic complications, including hepatitis and lung disease (SJIA-LD). On October 3-4, 2019, a two-day meeting, NextGen Therapies for Systemic Juvenile Idiopathic Arthritis (SJIA) & macrophage activation syndrome (MAS) organized by the Systemic JIA Foundation ( www.systemicjia.org/ ) in Washington, DC brought together scientists, clinicians, parents and FDA representatives with the objectives (1) to integrate clinical and research findings in MAS and SJIA-LD, and (2) to develop a shared understanding of this seemingly new pulmonary complication of SJIA. The current manuscript summarizes discussions and conclusions of the meeting.